FAKTOR-FAKTOR YANG MEMPENGARUHI DIVIDEND POLICY PADA PERUSAHAAN INDUSTRI KEUANGAN - Veronica Agatha Lionawan; Widyasari Widyasari (Fakultas Ekonomi, Universitas Tarumanagara, 2023)
This research of this study is to obtain empirical evidence regarding the effect of institutional ownership, managerial ownership, foreign ownership, and profitability on dividend policy. This study used 11 data samples of financial industry companies listed on the Indonesia Stock Exchange from the period of 2017-2020. This study uses Eviews 12 software as data processing. The research methodology used is statistical analysis method. Multiple linear regression analysis is used to test the hypothesis. Purposive sampling is used as a sampling technique in this study according to predetermined criteria. The results of this study indicate that institutional ownership, managerial ownership, foreign ownership, and profitability had no effect on dividend policy. The implication of this research is the need to improvecompanies in determining strategies, conducting optimal supervision, have a good company performance, and generate profits effectively to improve dividend policy.